ANALYSIS OF PHYSICAL FITNESS LEVELS OF CLASS V STUDENTS OF SDN GISIKDRONO 02 REVIEWED FROM NUTRITIONAL INTAKE, BMI AND PJOK VALUE - Allif Nafiiah; Rahardjo, Hermawan Pamot (Universitas Negeri Semarang, 2024)
Physical fitness in elementary school is an educational process carried out consciously and systematically through various physical activities in order to acquire abilities and skills, physical growth, intelligence and attitude growth. This study aims to analyze (1) Analyze the condition of physical fitness in terms of nutritional intake in Class V students at SDN Gisikdrono 02, (2) Analyze the condition of physical fitness in terms of BMI in Class V students at SDN Gisikdrono 02, (3) Analyze the condition of physical fitness in terms of from PJOK scores for Class V students at SDN Gisikdrono 02. This type of research uses descriptive quantitative. The population of this study was 97 students. The sample from this research was all class V students at SDN Gisikdrono 2, Semarang City, totaling 97 students. Data collection techniques in this research were carried out using questionnaires, interviews and documentation. The technique for analyzing nutritional intake data and BMI data uses the nutrisurvey2007.exe application. Meanwhile, student physical fitness data is obtained using the Indonesian Student Fitness Test (TKSI) by the Ministry of Education and Culture which has been tested as valid and reliable. A total of 21 female students and 18 male students had nutrition above the Recommended KKAL, and 27 female students and 31 male students had nutrition below the Recommended KKAL. Meeting calorie needs will help students stay fit and focused during study hours. A total of 22 female students and 29 male students have bodies with thin criteria, as many as 20 female students and 13 male students have bodies with normal criteria, and as many as 6 female students and 7 male students have bodies with fat criteria. By knowing their BMI and paying attention to their health, students can increase their chances of succeeding in school. A total of 4 female students and 8 male students had PJOK score criteria in the very good category, as many as 44 female students and 41 male students had PJOK score criteria in the good category. By knowing their PJOK scores, students can evaluate their physical health. This helps in monitoring their physical abilities and athletic progress. Conclusions: (1) There is a relationship between students' nutritional intake and physical fitness level, (2) There is a significant relationship between students' BMI and physical fitness level, (3) There is a significant relationship between grades in PJOK subjects and physical fitness level.